Pengaruh Pengetahuan Perpajakan, Sosialisasi Perpajakan, dan Kemudahan Persyaratan Perpajakan Terhadap Pem-anfaatan Insentif PPh Final UMKM PMK No.82/Pmk.03/2021 (Studi Kasus Pada Wajib Pajak Umkm di Kota Malang) - Salisa, Meilenia Rahma; Prastiwi, Arum (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to analyze and examine the effect of tax application, socialization, and ease of application of MSME final income tax incentives. The MSME final income tax incentives policy is a government policy to provide a stimulus in the form of reducing taxes that must be paid by MSMEs in the context of decreasing the national economy and as a response to the government's productivity. Data were obtained from MSME taxpayers in Malang City using a convenience sampling method. This study uses a survey method that is distributed online and directly by visiting MSMEs in Malang City to collect respondent data. The data that can be processed in this study are 100 questionnaires or 84% of the number of questionnaires distributed by researchers. Testing the data in this study using multiple linear regression analysis. The results showed that the knowledge of taxation, socialization of taxation, and ease of taxation were significant in the utilization of MSME final income tax incentives in Malang City. In addition, socialization is the variable that has the most influence on the utilization of MSME final income tax incentives, so it is necessary for the Directorate General of Taxes to increase the socialization of final income tax incentives and also to expand the network and media of tax socialization.